Testing The Effectiveness Of Formulation Herbicide On Weeds In Multi Locations - Risvan Anwar; Eka Suzanna; Djatmiko Djatmiko (University of Prof. Dr. Hazairin, SH, 2021)
Previous research has found a new type of herbicide made from fermented coconut water as the main raw material, containing organic materials, microorganisms, and is environmentally friendly. A series of tests need to be done to see its effectiveness. This study aims to determine the best formulation of herbicide in controlling weeds on land weeds and aquatic weeds in multiple locations. The experiment used a randomized block design, consisting of nine treatments of herbicide formulation (Unihaz) with three replications. The treatments were Unihaz 1, Unihaz 2, Unihaz 3, Unihaz 4, Unihaz 5, Unihaz 6, Unihaz 7, Unihaz 8 (glyphosate 2 kg ha-1) and Unihaz 9 (fermented coconut water). The results of the study concluded that the Unihaz 7 formulation was effective in controlling weeds both in dryland (land weeds) and in wetlands (water weeds) at various altitudes, and could control weeds above 90%. The herbicide formulation of Unihaz 7 was better at controlling weeds in paddy fields than the use of glyphosate at a dose of 2000 g ha-1